Developing of Worksheets on Single and Group Data with A Basketball Context - Meida Rosita; Kiki Nia Sania Effendi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to develop worksheets in the context of basketball on single data and group data with valid and practical criteria, which have the potential to have a positive impact on mathematics learning. The research used a development studies type of design research approach, which included three stages, namely the introduction stage, the prototype stage, and the assessment stage. Formative evaluation was applied through self evaluation, expert review, one-to-one evaluation, small group trials, and field test. The research instruments included documentation, interviews, and practicality questionnaires that were analyzed. The research subjects were eighth-grade students at a junior high school in Karawang. The results showed that the developed worksheet met the criteria of validity, practicality, and effectiveness. Students showed high enthusiasm in participating in learning activities because the basketball context used made learning activities more meaningful, enjoyable, and easy to understand. Based on data analysis, the basketball-based worksheet was declared valid and practical for use in statistics learning in junior high schools. This product has the potential to improve the achievement of learning objectives related to data types in statistics.